TEKNIK EKSTRAPOLASI RICHARDSON BERULANG PADA MODEL BINOMIAL FLEKSIBEL UNTUK MENENTUKAN HARGA OPSI JUAL AMERIKA - , ARUM HANDINI PRIMANDARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis presents repeated Richardson extrapolation for pricing American put option. We apply Richardson extrapolation on the sequence of approximation of option value for accelerating the rate of its convergence. First, we define the sequence of approximation using flexible binomial model. A number of time step used in this scheme are based on the stepsize characterized by sequence of integers. Second, we extrapolate the sequence of approximation repeatedly. As the result, repeated Richardson extrapolation technique works on flexible binomial model can be used to accelerate the sequence of approximation produced by this scheme so that we merely need a less of time step for pricing option.